Reflective Practice in ITE-Exploring the Perspectives of University and School Based Teacher Educators - Ni Dhuinn, Melanie; Liston, Jennifer; Prendergast, Mark; Kaur, Tandeep (My University, 2020)
Darling Hammond (2017) reports how teacher effectiveness has rapidfly risen to the top of policy agendas globally. She contends that teacher preparation and development are key building blocks in developing effective teachers. Hall et al (2018) highlight how critical reflection is prioritized as being central to the development of one's competence as a teacher and professional. Reflective practice (RP) is a core element of the elarning journey that PSTs embark on through ITE programmes. In terms of the place of RP within the ITE curriculum it is frequently positioned amongst the plan-teach-reflect cycle. However, research has evidenced that it often becomes the more subdued component of this cyclical journey (McGarr & Moody 2010, Bolton 2005). Dewey (1933) describes reflection as a holistic approach to addressing problems in practice rather than a series of steps or proecedures to be used by teachers. Zeichner and Liston (1996, p.20) extend on Dewey's work and suggest the social, moral and political aspects of teaching require consideration; "Reflective teaching entails a recognition, examinations, and rumination over the implications of one's beliefs, experience, attitudes, knowledge, and values as well as the opportunities and constraints provided by the social conditions in which the teacher works".
American Educational Research Association, The Power and Possibilities for the Public Good When Researchers and Organisational Stakeholders Collaborate
Keywords: EDUCATION; Education and Work; Children; Employment; Relationships